2002
DOI: 10.1016/s0005-2728(02)00257-8
|View full text |Cite
|
Sign up to set email alerts
|

Structure, subunit function and regulation of the coated vesicle and yeast vacuolar (H+)-ATPases

Abstract: The vacuolar (H(+))-ATPases (or V-ATPases) are ATP-dependent proton pumps that function to acidify intracellular compartments in eukaryotic cells. This acidification is essential for such processes as receptor-mediated endocytosis, intracellular targeting of lysosomal enzymes, protein processing and degradation and the coupled transport of small molecules. V-ATPases in the plasma membrane of specialized cells also function in such processes as renal acidification, bone resorption and pH homeostasis. Work from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
23
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 38 publications
2
23
0
1
Order By: Relevance
“…This binding does take place (Fig.·2), which means that subunit G is exposed in the VATPase complex, which supports previous results obtained from studies on accessibility to trypsin cleavage (Gruber et al, 2000). The bound antibody did not inhibit the activities of the Vma10p-HA-containing V-ATPase (Figs·3, 4) which is in agreement with Vma10p being a part of the stator, and not participating in the rotor apparatus, as previously suggested (Nelson and Harvey, 1999;Charsky et al, 2000;Arata et al, 2002). It appears that the G subunit is present at 2-3 copies per complex (Supekova et al, 1995;Hunt and Bowman, 1997).…”
supporting
confidence: 90%
See 1 more Smart Citation
“…This binding does take place (Fig.·2), which means that subunit G is exposed in the VATPase complex, which supports previous results obtained from studies on accessibility to trypsin cleavage (Gruber et al, 2000). The bound antibody did not inhibit the activities of the Vma10p-HA-containing V-ATPase (Figs·3, 4) which is in agreement with Vma10p being a part of the stator, and not participating in the rotor apparatus, as previously suggested (Nelson and Harvey, 1999;Charsky et al, 2000;Arata et al, 2002). It appears that the G subunit is present at 2-3 copies per complex (Supekova et al, 1995;Hunt and Bowman, 1997).…”
supporting
confidence: 90%
“…Further analysis showed that the N terminus of the G subunit might fold into an α helix in which one face has highly conserved residues in both the V1 G and F0 b subunits (Hunt and Bowman, 1997). Because of this structural resemblance, it was suggested that subunit G, together with subunit E, act like a 'hook' or a 'stator' similar to b in F-ATPase (Nelson and Harvey, 1999;Arata et al, 2002). Mutational analysis of the conserved face of the G subunit α helix revealed that several mutations were tolerated and even stabilized the complex, while others rendered the complex unstable (Charsky et al, 2000).…”
mentioning
confidence: 99%
“…3B). We and others 3 have noted that all the available antibodies to a1 show a weak signal 3 U. Kornak, personal communication. (lanes 2, 4, 6, and 8) using an affinitypurified antibody raised against two different G3 peptide sequences.…”
Section: Confirmation Of G3-a4 Interaction and Analysis Of Possible Imentioning
confidence: 96%
“…In the current structural model of the H ϩ -ATPase, the peripheral V 1 (hydrolytic) domain contains 3A, 3B, one each of C, D, E, F, and H, and two G subunits. This is loosely linked to the membrane-anchored V 0 domain by two stalks; the central stalk consists of the D and F subunits, and the peripheral stalk contains the C, E, G, and H subunits together with the N terminus of the a subunit (1)(2)(3)(4). The a subunit is present as a single copy in the V 0 domain along with single copies of the d and e subunits and a ring structure comprising multiple numbers of c and cЈ (in yeast cells) and a single cЉ subunit (1,3,5,6).…”
mentioning
confidence: 99%
“…The role of the other V 1 subunits is not so clear. It is thought that the central stalk may be composed of D (32 kDa) and F (14 kDa) subunits (8,9). The stator region is thought to be composed of E (27 kDa), G (13 kDa), C (42 kDa), and H (54 kDa) subunits (9 -13).…”
mentioning
confidence: 99%